Global citizenship education and English as a lingua franca - Fan (Gabriel) Fang (Universitas Islam Malang, 2019)
Currently, how English is being used as a lingua franca (ELF) has caused linguistic and cultural norms to be revisited in relation to language use. The issue of global citizenship has emerged when English is used as the main medium of instruction in higher education; as achieving global citizenship is a main goal of international universities, the ELF paradigm has assisted in the realization of this goal because English is used in a fluid and dynamic perspective. This paper uses interview data (N=6), which was collected from Chinese students from the Chaoshan area who obtained their master’s degrees abroad, to analyze how these students developed their senses of global citizenship. Although their ELF experiences play an important role in understanding global citizenship, many did not receive a formal education regarding global citizenship at home or abroad. This paper concludes by emphasizing how the ELF paradigm can aid higher education institutions raise people’s awareness of global citizenship.